Description Of Urinary Incontinence And Psychosocial Problems In The Elderly In The Working Area Of Puskesmas Lanrisang Pinrang District - Jurana Jurana; Abdul Majid; Nurlaila Fitriani (FAKULTAS DAKWAH UIN SALATIGA, 2024)
The increasing pace of life, social pressures and the aging population are causing urinary incontinence and psychosocial problems in the elderly to increase. Although not a fatal condition, urinary incontinence can impair mental health and reduce quality of life, as well as increase the risk of depression and anxiety. The study focused on knowing the description of urinary incontinence and psychosocial problems in the elderly in the working area of Puskesmas Lanrisang Pinrang Regency. This cross-sectional descriptive study involved 90 elderly respondents from the Lanrisang Health Centre, selected using purposive sampling based on specific inclusion and exclusion criteria. Data were collected using validated questionnaires: the Questionnaire for Urinary Incontinence Diagnosis (QUID) and Depression Anxiety Stress Scale 21 (DASS 21). QUID was selected for its specificity in categorizing different types of urinary incontinence, making it a reliable tool for this population. Similarly, DASS 21 is well-regarded for its ability to measure stress, anxiety, and depression levels comprehensively, which are critical psychosocial factors examined in this study. These tools were chosen for their reliability in measuring urinary incontinence and psychosocial problems, with analysis performed using univariate methods. The results showed that the majority of respondents (40.0%) experienced mixed urinary incontinence. The prevalence of urinary incontinence in the elderly with moderate levels of stress, anxiety, and depression was higher compared to mild and severe levels of stress, anxiety, and depression.